Twin Pregnancy discordordant for Downs syndrome: Case Report - Albu, Dinu-Florin; Albu, Cristina-Crenguta; Albu, Stefan-Dimitrie (International Journal of Medical Research and Review, 2015)
The work presented is a clinical and genetical trial of a couple with a reproductive failure and a family history of chro-mosomal abnormalities. The most reliable and accurate methods used for antenatal diagnosis of Down syndrome fetuses are highlighted.